Glucose Increase DAGLα Levels in Tanycytes and Its Inhibition Alters Orexigenic and Anorexigenic Neuropeptides Expression in Response to Glucose - Palma-Chavez, Alejandra; Konar-Nié, Macarena; Órdenes, Patricio; Maurelia, Felipe; Elizondo-Vega, Roberto; Oyarce, Karina; López, Sergio; Rojas, Joaquin; Steinberg, Ximena; García-Robles, María A.; Sepúlveda, Fernando J. (Frontiers in Endocrinology, 2019)
The endocannabinoid system (ECS) is composed of a group of Gi-coupled protein receptors and enzymes, producing and degrading the endocannabinoids, 2-arachidonoylglycerol (2-AG) and N-arachidonoyl-ethanolamine (AEA). Endocannabinoid-mediated signaling modulates brain functions, such as pain, mood, memory and feeding behavior. The activation of the ECS is associated with overeating and obesity; however, the expression of components of this system has been only partially studied in the hypothalamus, a critical region implicated in feeding behavior. Within this brain region, anorexigenic and orexigenic neurons of the arcuate nucleus (ARC) are in close contact with tanycytes, glial radial-like cells that line the lateral walls and floor of the third ventricle (3V). The specific function of tanycytes and the effects of metabolic signals generated by them on adjacent neurons is starting to be elucidated. We have proposed that the ECS within tanycytes modulates ARC neurons, thus modifying food intake. Here, we evaluated the expression and the loss of function of the 2-AG-producing enzyme, diacylglycerol lipase-alpha (DAGL𝛼). Using Western blot and immunohistochemistry analyses in basal hypothalamus sections of adult rats under several glycemic conditions, we confirm that DAGL𝛼 is strongly expressed at the basal hypothalamus in glial and neuronal cells, increasing further in response to greater extracellular glucose levels. Using a DAGL𝛼-inhibiting adenovirus (shRNA), suppression of DAGL𝛼 expression in tanycytes altered the usual response to intracerebroventricular glucose in terms of neuropeptides produced by neurons of the ARC. Thus, these results strongly suggest that the tanycytes could generate 2-AG, which modulates the function of anorexigenic and orexigenic neurons.